Sosialisasi dan Pembinaan Kedisiplinan Santri dalam Mengikuti Kegiatan Pondok Pesantren di Bantul - Hodiri Adi Putra; Parmadi Sigit Purnomo; Dwi Suharyanta; Virda Rahmatunnisa; Reqy Syafira Nurafifah Sumarna (Edujavare Publishing, 2023)
Discipline development for students is the most effective means in the educational process at Islamic boarding schools, which lasts for a day and a night, all of this cannot be separated from the people involved, from administrators, students, teachers, and Islamic boarding school caregivers, who can follow it well. The aim of this service is to increase the knowledge and awareness of students in improving their discipline in participating in activities at the Darul Hijrah Complex Islamic Boarding School. The Participatory Rural Appraisal (PRA) model is used in community service activities, prioritizing community empowerment to participate, in this case the Islamic Boarding School student community. This activity took the form of socialization and guidance to students regarding discipline which was carried out offline for 42 students. The media used are power point, laptop, LCD, and online quizzes using the Kahoot application. Measuring student discipline using a daily mutabaah book. The results of this service research show that the students are very enthusiastic about participating in activities and can easily understand material about discipline while accompanied by coaching, they can also organize themselves and can directly train and practice discipline in participating in activities at the Darul Hijrah Complex Islamic Boarding School. So, it can be concluded that the development of student discipline can be carried out continuously so that students can form better behavioral habits and easily participate in the activities of the Darul Hijrah Complex Islamic Boarding School.